Implementation of Educator Resources and Education Personnel at MTs YP. Ummul Quraa Tembung, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra Province - Azra Humaira; Fatin Syahirah; Salwa Nabila Damanik; Salwa Putri Verhan; M. Khalid Pay Hasibuan (Quality : Journal Of Education, Arabic And Islamic Studies, 2025)
This study aims to describe (1) resource planning for educators and education personnel, (2) recruitment and selection, and (3) training and development at MTs YP. Ummul Quraa. This type of research is descriptive with a qualitative approach. The research subjects consisted of the madrasah head and teachers. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman interactive analysis model. The results showed that (1) planning is done through deliberation with teachers to determine the qualifications needed, (2) recruitment and selection is done through disseminating vacancy information and interviews to ensure the suitability of candidates, and (3) training is done by recommending employees to attend external training to improve skills. MTs YP. Ummul Quraa continues to strive to improve the quality of teaching and education resources on an ongoing basis.